Comparisons of Four Acne Grading Systems Recommended in China, Korea, and Japan - Yu R; Chen M; Zhao H; Yang J; Li T; Cui Y (Dove Medical Press, 2023)
Ruixing Yu,1 Miao Chen,2 Huijuan Zhao,3 Jungang Yang,1,4 Tong Li,5 Yong Cui1 1Department of Dermatology, China-Japan Friendship Hospital, Beijing, People's Republic of China; 2Department of Dermatology, Zhuozhou City Hospital, Zhuozhou, Hebei, People's Republic of China; 3Department of Dermatology, China Aerospace Science and Industry Group 731 Hospital, Beijing, People's Republic of China; 4Peking University China-Japan Friendship School of Clinical Medicine, Beijing, People's Republic of China; 5Department of Dermatology, Baoji Traditional Chinese Medicine Hospital, Baoji, Shaanxi, People's Republic of ChinaCorrespondence: Yong Cui, Department of Dermatology, China-Japan Friendship Hospital, Beijing, People's Republic of China, Email wuhucuiyong@vip.163.comIntroduction: Acne vulgaris is one of the most prevalent skin disorders. The treatment regimen depends on how severe the AV is. The acne grading system is crucial for clinical and research work. The aim of this work was to evaluate intra-grader differences between 5 investigators using Acne Grading System (AGS), the International Improved Grading System (IIGS), the Korean Acne Grading System (KAGS), and the Japanese Acne Grading System (JAGS) to assess acne vulgaris (AV) severity.Patients and Methods: AV sufferers from dermatological clinics of five hospitals in China were the subject of a prospective cross-sectional study. AGS, IIGS, KAGS and JAGS were utilized by 5 investigators to verify the severity of AV. The correlation between AGS, IIGS, KAGS and JAGS was examined.Results: A complete of 1107 AV sufferers were enrolled in the study. There were indications that the AGS, IIGS, KAGS and JAGS had sufficient internal consistency. As for the reliability amongst raters, AGS, IIGS, KAGS and JAGS confirmed gorgeous reliability. There were strong correlations amongst AGS, IIGS, KAGS and JAGS (P≤ 0.01). The interior reliability of investigator 1 one year ago and later after usage of AGS and IIGS was excellent (P≤ 0.01).Conclusion: IIGS and AGS exhibited great correlation with KAGS and JAGS and were highly reliable.Keywords: acne vulgaris, acne grading system, assessment, severity